Planners, navigators, and pragmatists: collaborative wayfinding using a single mobile phone - Reilly, Derek; Mackay, Bonnie; Watters, Carolyn; Inkpen, Kori (Personal and Ubiquitous Computing, 2009)
Shared use of mobile devices is increasingly prevalent in both research prototypes and in practice, however, little is known as to how to support best this interaction paradigm. In this paper, we present a study examining how pairs share a single mobile phone during a collaborative wayfinding activity. We provide a classification of strategies, role relationships and phone interactions employed to conduct the wayfinding activities in our study. While acknowledging that the factors determining how the phone was shared are nuanced and intertwined, our results illustrate how differences in the mobile application's interface influenced shared use, wayfinding strategy and outcome.